Hadist Tentang Penjualan Berdasarkan Kesepakatan Bersama, Dalam Konteks Kehidupan Kontemporer - Heri Purnomo; Mohamad Anton Athoillah; Muhamad Dede Rodliyana (Yayasan Cendekia Gagayunan Indonesia, 2025)
Hadiths are one of the most important sources of Islamic law, including in economic matters, especially in buying and selling transactions. Sales based on mutual agreement is a fundamental principle described in various traditions. In the context of contemporary life, this principle is relevant in various modern business models, both in physical and digital transactions. This article examines the relevance of the traditions governing sale and purchase transactions in the context of the modern economy taking into account the dynamics of technological development, e-commerce, and the need for transparency in transactions. It highlights how the application of these principles can ensure justice for all parties involved in the buying and selling process, avoid usury, and promote economic balance. Based on the views of two Islamic economists, namely Muhammad Abdul Mannan and M.A. Chapra, this study also reveals how the principle of mutual agreement can be applied in increasingly complex contemporary businesses.